Peramalan Produksi Gula Pasir Menggunakan Fuzzy Time Series Dengan Optimasi Algoritma Genetika (Studi Kasus PG Candi Baru Sidoarjo) - Afif Ridhwan; Dian Eka Ratnawati; Bayu Rahayudi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Production planning is done by PG Candi Baru Sidoarjo every year as an effort for improving the quality as consumers demand continues to increase. To optimize the production strategy PG Candi Baru should be able to estimate the next production target based on existing historical data. With fuzzy time series method which is optimized by Genetic Algorithm method, the writer wants to help solving the problem to predict the production of sugar, hopefully the research result can help as reference to be used as consideration to determine the amount of sugar production for the next month. Based on the result of testing the accuracy of predictive results using Mean Absolute Percentage Error (MAPE) method obtained the percentage of error rate 1.9% which means the qualification is good.